Assessing sediment pollution by applying some geochemical indices for Al-Wind River banks/ East of Iraq - Al-Ali, Iman A. (Iraqi Journal of Science, 2019)
15 sediment samples were collected; 8 samples from the eastern bank, and 7 samples from the western bank of Al-Wind River in Diyala governorate to assess the sediment pollution in some trace elements such as Fe, Ni, Cd, Zr, Zn and Cu in addition to some oxides such as Al2O3, CaO, Na2O and K2O to find the effect of anthropogenic pollution and the industrial production on the sediment closed especially Naftkhana by using some geochemical pollution indices such as: geoaccumulation factor (I-geo), enrichment factor (EF),contamination factor (CF), pollution loud index (PLI) and to evaluate the degree of weathering by Applying the Chemical Index of Alteration (CIA)in both banks of Al-Wind River. The results of general contamination factors indicate that the eastern bank of Al-Wind River especially that closed by Naftkhana area having quite more concentrations of trace element and oxides from the western bank. The results of I-geo presents unpolluted sediment with Pb and Fe and slightly polluted with Zn, Cu, and Ni in both banks, while the western bank in some locations recorded of moderately polluted sediments with Ni and slightly to moderately polluted sediments with Cu and Zn and reach moderately severely polluted in the eastern bank. The contamination factor (CF) for Ni and Zr classified as class 2 which indicate moderately contamination to severely pollute in both banks, while Fe, Pb, Cu and Zn conbankred unpolluted in both banks. Enrichment factor (EF) for Fe, Pb, Zr and Cu are conbankred deficiency to low enrichment the range of natural variability, while Ni record high values reached to 6.4 indication of anthropogenic inputs. Pollution load Index (PLI) is perfection and classified as class 0 in both banks. Chemical index of alteration (CIA) reflecting the chemical weathering intensity especially for the western bank.